STRUCTURAL PERFORMANCE DUE TO ENGINE VIBRATION USING THE LEVELLING TIME HISTORY METHOD - Ahmad Yudi; Andrew Andonia First Purba; Ade Prayoga Nasution; M. Abi Berkah Nadi; Siska Apriwelni; Alfinna Mahya Ummati; Kirtinanda, Kirtinanda (Nusantara Hasana Journal, 2025)
In this case study, earthquake is one of the loads that is considered in designing and analyzing buildings. So that the earthquake becomes the author's calculation in analyzing the building against the strength and safety of the structure in receiving earthquake loads that occur with the anticipation of another earthquake history such as the El Centro earthquake. The author aims to analyze the performance of the structure that occurs against earthquake loads, the analysis also pays attention to the level of value that can be achieved by the building nonlinearly, namely the increase in the value of the initial acceleration of the earthquake (Level Aog) that occurred. The analysis is carried out on steel buildings that have bracing, concrete reinforcement, and there are machine activities. Structural performance analysis uses numerical methods and iterations which are assisted by a structural analysis program. The analysis is carried out by defining the hinge on the structural element. The analysis process is carried out in stages with the condition of the machine which is also considered in the leveling time history method. Time history which is also a history of vibration and machine vibration activity adds to the input parameters of the analysis carried out on the building. The response of the building due to engine vibration will be compared with the condition of the building when the engine is off which does not cause vibration. Structural performance analysis is carried out by increasing Aog until the structural elements of the building are no longer able to withstand shear forces and loads that occur when severe damage or conditions are above Collapse Prevention (CP). The results of the structural analysis will produce output in the form of Aog levels with plastic checks with color visuals, deviation checks and rotation checks based on FEMA 356 so as to produce structural strength capabilities. Based on the vibrations that occur with machine activity, the frequency can still be held by the building. The machine vibrations that occur, dampen the vibrations caused by the earthquake so that the leveling indicator becomes larger.